A Closer Look at Seborrheic Keratoses: Patient Perspectives, Clinical Relevance, Medical Necessity, and Implications for Management - Del Rosso, James Q. (J Clin Aesthet Dermatol, 2017)
The author sought to discover why seborrheic keratoses that are not symptomatic or clinically suspicious are not considered therapeutically important to most clinicians. The author conducted an office-based, observational study examining how the diagnosis of asymptomatic seborrheic keratoses personally affects patients and what these patients think concerning treatment. Many patients reported being bothered by the diagnosis of seborrheic keratoses, even when told it’s not cancerous, and indicated an interest in its treatment. Lack of insurance coverage for the treatment of non-symptomatic seborrheic keratoses may be the primary reason clinicians do not consider seborrheic keratoses therapeutically important, as clinicians often find the discussion of “self payment” with their patients to be awkward. Furthermore, patients may not understand the implications that “lack of medical necessity” may have on their treatment options. The author describes a clinical approach that may better serve patients and clinicians through the compartmentalization of asymptomatic seborrheic keratoses treatment as a cosmetic procedure within the clinical practice model.